مواقف الولايات المتحدة الأم ريكية اتجاه الثورة 19 -1954 الجزائرية 62 - - عمران عثماني; - د.محمود علالي (جامعة عمار ثليجي الاغواط, 2023)
ملخص المذكرة: تتناول هذه الدراسة موضوع المواقف الأمريكية من الثورة الجزائرية. وقبل الخوض في موضوع المواقف من الثورة تطرقنا إلى الموقف الأمريكي من القضية الجزائرية قبل اندلاع الثورة. ففي الفصل التمهيدي بدأنا بتسليط الضوء على العلاقات الجزائرية الأمريكية و تطوراتها قبل الاستعمار الفرنسي ثم تطرقنا إلى دراسة الموقف الأمريكي من الاحتلال الفرنسي للجزائر ومنها ذهبنا إلى ذكر لاتصالات قادة ا كلا العمل الوطني بشخصيات أمريكية رسمية فذكرنا من "الأمير عبد القادر " ومن بعده حفيده "الأمير خالد" ثم "فرحات عباس " وجماعته, والموقف الأم ريكي من القضية 1 الجزائرية قبل اندلاع الثورة التحريرية وتمثلت في الموقف من مجازر الثامن ماي , وتطرقنا في 945 الفصل الأ ول إلى دراسة المواقف الأمريكية الرسمية تجاه الثورة الج زائرية وينقسم إلى مبحثين؛ تناولنا في المبحث الأول المواقف الأمريكية الرسمية المعادية للثورة و المدعمة للطرف الفرنسي ومنها ذهبنا إلى إبراز المساعي الجزائرية في محاولة لتحييد الطرف الأمريكي في الن زاع, أما المبحث الثاني فيتناول المواقف الأمريكية الرسمية المساندة للثورة الجزائرية. أما الفصل الثاني فخصصناه بدراسة المواقف غير الرسمية وهو بدوره يشمل مبحثين: تضمن الأول مواقف التنظيمات الطلابية والنقابات العمالية الأمريكية وتضمن المبحث الثاني ردود الفعل من قيام الثورة الجزائرية من خلال الصحافة الأم ريكية ٠من معادية و مساندة ملخص Summary 178 This study deals with the subject of American attitudes towards the Algerian revolution. Before delving into the subject of attitudes towards the revolution, we discussed the American position on the Algerian issue before the outbreak of the revolution. In the introductory chapter, we began to shed light on the Algerian-American relations and their developments before French colonialism, then we touched on the study of the American position on the French occupation of Algeria, including we went to mention the contacts of the leaders of the national action with official American figures, so we mentioned both "Prince Abdelkader" and then his grandson, "Prince Khaled", then "Farhat Abbas" and his group, and the American position on the Algerian issue before the outbreak of the liberation revolution, represented in the position of the massacres of the eighth of May.In the first chapter, we dealt with the study of the official American positions towards the Algerian revolution and is divided into two sections; we dealt in the first section with the official American positions against the revolution and supporting the French party, including we went to highlight the Algerian efforts in an attempt to neutralize the American party in the conflict, while the second section deals with the official American positions in support of the Algerian revolution. The second chapter is devoted to the study of informal positions, which in turn includes two sections: the first included the positions of student organizations and American trade unions and the second section included reactions to the Algerian revolution through the American press of hostility and support.